Determinants of financial literacy and behavioral bias among adolescents - Marco Aschenwald; Armando Holzknecht; Michael Kirchler; Michael Razen (University of Innsbruck, Research Platform Empirical and Experimental Economics (eeecon), 2023)
Building on cross-sectional data for Austrian high school students from fifth to twelfth grade, we investigate the correlations between socio-economic background variables and a comprehensive set of variables related to financial decision-making (i.e., financial knowledge, behavioral consistency, economic preferences, field behavior, and perception of financial matters). We confirm the findings of previous literature that the male gender is positively associated with financial knowledge and risk-taking and that there is a strong and beneficial correlation between math grades and healthy financial behavior (e.g., saving). Moreover, we find that students' behavioral consistency is positively correlated with measures of financial attitude (e.g., self-assessed future financial well-being and financial education received from parents). Finally, our results indicate that financial education, as perceived by the students, is primarily provided by parents.
Keywords: C93; D81; D91; G53; J13; 330; financial literacy; behavioral biases; economic preferences; field behavior; perception; experiment; adolescents